2021
DOI: 10.3389/fphys.2021.715096
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ischemia During Rest Intervals on Bar Velocity in the Bench Press Exercise With Different External Loads

Abstract: The main aim of the present study was to evaluate the acute effects of ischemia used during rest periods on bar velocity changes during the bench press exercise at progressive loads, from 20 to 90% of 1RM. Ten healthy resistance trained men volunteered for the study (age = 26.3 ± 4.7 years; body mass = 89.8 ± 6.3 kg; bench press 1RM = 142.5 ± 16.9 kg; training experience = 7.8 ± 2.7 years). During the experimental sessions the subjects performed the bench press exercise under two different conditions, in a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 61 publications
2
19
1
Order By: Relevance
“…They embody the global reach of sports by captivating diverse participants and audiences from across the globe. In contemporary times, global sporting events are not only acknowledgements of athletic accomplishments but also significant economic occurrences, shaping the reputation of nations worldwide and leaving an enduring impact on the fields of politics, culture, and trade (Jarosz et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…They embody the global reach of sports by captivating diverse participants and audiences from across the globe. In contemporary times, global sporting events are not only acknowledgements of athletic accomplishments but also significant economic occurrences, shaping the reputation of nations worldwide and leaving an enduring impact on the fields of politics, culture, and trade (Jarosz et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, most significantly, the combination of neurotic (organic) and psychopathological syndromes is distinctive in the context of PTSD, as overt neurotic (or behavioral) disorders can hide clinically less obvious neurotic (organic) symptoms, while serious neurological disorders can mask serious PTSD. In this case, organic neurological symptoms gradually decrease, and all manifestations of vascular pathology gradually become prominent and visible, becoming the main pathogenetic factor that eventually causes clinical decompensation of the affected person (Messina et al, 2015; Jarosz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown conflicting results regarding the effects of IPC on subsequent performance. Some authors found no difference between the IPC protocol (220 mmHg of cuff pressure) and a sham condition (20 mmHg of cuff pressure) (Marocolo et al, 2016a;Marocolo et al, 2016b), while others reported acute increases in strength and power performance (Paradis-Deschênes et al, 2016;de Oliveira Cruz et al, 2019;Jarosz et al, 2021;Wilk et al, 2021). For example, Marocolo et al (Marocolo et al, 2016a) evaluated the effects of IPC (4 × 5-min occlusion at 220 mmHg) and a sham condition on resistance exercise performance in the lower and upper limbs and found that both IPC or sham may enhance performance during resistance exercise with no difference between them.…”
Section: Discussionmentioning
confidence: 99%